Reading Bonhoeffer amid the Hong Kong Protests. (July 2021) - Lam, Jason
Abstract : This essay reflects on how the people of Hong Kong have read the life and thought of Dietrich Bonhoeffer and found inspiration for their own struggle against authoritarianism, specifically following the pro-democracy movement in recent years. The purpose here is not to offer a first-hand interpretation of Bonhoeffer's works, but rather to present a historical exercise in sorting through contextual readings of Bonhoeffer. In what follows we will first offer a review of the church's participation in the protests that took place in Hong Kong during the second half of 2019 and articulate the relevance of Bonhoeffer's thought for the situation. Secondly, we will reflect on several important concepts concerning how Bonhoeffer transformed from a seeming 'pacifist' into a participant of the anti-Nazi movement. Next, some important figures involved in the Hong Kong democracy movement who are interested in Bonhoeffer will be examined. They are not Christians in the usual sense and thus offer us a good opportunity for examining why Bonhoeffer's late thought can gain 'this-worldly' acceptance. Interestingly, through this process we find that the particular contextual reading conditioned by Hong Kong's recent socio-political turbulence has offered occasions to rethink and develop some of Bonhoeffer's important concepts treated in existing scholarship. 1